THE ROLE OF SOLAR CONCENTRATORS IN INDUSTRIAL THERMAL ENERGY - Sharibayev Nasir Yusupjanovich , Makhmudov Bekzod Mirzaakhmad ugli (Research Focus International Scientific Journal, 2025)
Solar concentrators play a crucial role in industrial thermal energy applications by efficiently capturing and converting solar radiation into high-temperature heat. These systems enhance the feasibility of renewable energy integration in industrial processes by providing a sustainable and cost-effective alternative to conventional fossil-fuel-based thermal energy sources. Various types of solar concentrators, including parabolic troughs, linear Fresnel reflectors, solar towers, and dish systems, offer distinct advantages depending on the temperature and operational requirements of industrial processes. The implementation of solar concentrators in industries such as food processing, chemical manufacturing, and metal treatment contributes to reducing greenhouse gas emissions and energy costs while improving energy security. This paper explores the working principles, classifications, efficiencies, and real-world applications of solar concentrators in industrial settings, highlighting their potential to drive sustainable industrial development.